Misoginia e assédio sexual : um debate na arte contemporânea - Chagas, Jarina Oliveira (My University, 2018)
Considering the potential that arts have to interrogate the problematics of the contemporary world, in the paper ?Misogyny and Sexual Harassment: a debate in the contemporary art?, appropriate a personal object for myself resignifying it in my work. The object, a personal garment, that has never been worn before and that was kept by many years, carries the weight of a traumatic memories ?triggering? object and is presented to the audience after being transformed by my intervention. As a result of a long cathartic process, what was once the 15-years-old dress of a party that has never taken place turns into the ?Iron Lady? piece with the purpose of provoking an interrogative atmosphere (sic).
Considerando o potencial questionador da arte nas problemáticas do mundo contemporâneo, no trabalho ?Misoginia e Assedio Sexual: Um debate na arte contemporânea?, aproprio-me de um objeto pessoal ressignificando-o em minha obra. O objeto, uma vestimenta pessoal nunca antes usada e guardada por muitos anos, carrega o peso de ?gatilho? de memórias traumáticas e é apresentado ao público após ser transformado por minhas intervenções. Fruto de um longo processo catártico, o que outrora fora o vestido de 15 anos de uma festa que jamais aconteceu transforma-se na obra ?Dama de Ferro? com o intuito de provocar ruídos questionadores acerca do assédio sexual (sic).
Keywords: Misoginia; Assédio sexual; Catarse